Aberrant p16INK4A and DPC4/Smad4 expression in intraductal papillary mucinous tumours of the pancreas is associated with invasive ductal adenocarcinoma. Issue 6 (1st June 2002) - Biankin, A V; Biankin, S A; Kench, J G; Morey, A L; Lee, C-S; Head, D R; Eckstein, R P; Hugh, T B; Henshall, S M; Sutherland, R L
Abstract : Background and aims: Intraductal papillary mucinous tumours (IPMT) of the pancreas constitute a unique pathological entity with an overall incidence of associated invasive malignancy of 20%. The malignant potential of an individual IPMT cannot be accurately predicted. Preoperative estimation of the risk of associated invasive malignancy with IPMT would be of significant clinical benefit. As aberrations in cell cycle regulatory genes are associated with the progression of precursor pancreatic ductal lesions to invasive adenocarcinoma, we examined expression of key cell cycle regulatory genes in the cyclin D1/retinoblastoma pathway and the transforming growth factor β/Smad4 signalling pathway in a cohort of patients with surgically resected IPMT. Methods: Sections of formalin fixed paraffin embedded pancreatic tissue from a cohort of 18 patients with IPMT were examined using immunohistochemistry for protein expression of cell cycle regulatory genes p16 INK4A, p21 CIP1, p27 KIP1, cyclin D1, pRb, and p53, as well as the cell signalling molecule Smad4. A comparison of expression levels was made between adenoma/borderline IPMT (10 patients) and intraductal papillary mucinous carcinoma (IPMC) (eight patients, four of whom harboured invasive carcinoma). Statistical analysis was performed using the χ 2 and Fisher's exact tests. Results: Aberrant expression of the proteins examined increased in frequency from adenoma/borderline IPMT to IPMC. Specifically, there was a significantly greater incidence of loss of p16 INK4A expression in IPMC: 8/8 lesions (100%) compared with 1/10 (10%) adenoma/borderline IPMT (p<0.001). Similarly, loss of Smad4 expression was associated with IPMC: 3/8 (38%) versus adenoma/borderline IPMT 0/10 (p<0.03). Loss of Smad4 expression within the IPMT was the best marker for the presence of invasive carcinoma (p<0.001). Conclusions: These data indicate that loss of p16 INK4A and Smad4 expression occur more frequently in IPMC alone, or with associated invasive carcinoma, compared with adenoma/borderline IPMT. Aberrant protein expression of these cell cycle regulatory genes in IPMT and pancreatic intraepithelial neoplasia in the current model of pancreatic cancer progression suggest similarities in their development and may also represent the subsequent risk of invasive carcinoma.